(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article considers some patterns of behavior in late adolescence (18–23 years). Gender determinants and features of manifestation of individual style of behavior in conflict situations among young men and women are analyzed. The results of an empirical study aimed at identifying gender differences in students’ behavioral styles in conflict situations and the factors of such situations with the help of the author’s questionnaire are presented. The obtained data were expanded and refined by means of the tried and tested method “Determining the style of behavior in conflict situations” TCI Thomas — Kilman